ANALISIS PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MENYIKAPI KURANGNYA KARAKTER SISWA KARENA GAME ONLINE - Yunita Tumonglo; Santi Tanggo, Yudith Tandi Belopa, Junike Limbong, Fredianto Rerung (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The phenomenon of weakening student character in the digital era is a serious challenge in the world of education, especially in the context of technological developments and popular culture such as online games. This study aims to analyze the strategic role of Christian Religious Education teachers in responding to the decline in student character caused by online game addiction. The research method used is library research with a qualitative approach, reviewing various relevant theological, pedagogical, and psychological literature. The results of the study show that online games contribute to reduced discipline, empathy, responsibility, and self-control of students. In this context, Christian Religious Education teachers have the responsibility as educators, moral educators, and spiritual guides. Effective strategies include the integration of Christian values in the learning process, the formation of ethical digital literacy, a contextual pastoral approach, and collaboration between schools, families, and churches. With the right and faith-based strategy, Christian Religious Education teachers can act as agents of transformation that shape students' character holistically amidst the challenges of today's digital culture